2016
DOI: 10.1088/0965-0393/24/7/075006
|View full text |Cite
|
Sign up to set email alerts
|

Linking simulations and experiments for the multiscale tracking of thermally induced martensitic phase transformation in NiTi SMA

Abstract: Martensitic phase transformation in NiTi shape memory alloys (SMA) occurs over a hierarchy of spatial scales, as evidenced from observed multiscale patterns of the martensitic phase fraction, which depend on the material microstructure and on the size of the SMA specimen. This paper presents a methodology for the multiscale tracking of the thermally induced martensitic phase transformation process in NiTi SMA. Fine scale stochastic phase field simulations are coupled to macroscale experimental measurements thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(71 citation statements)
references
References 74 publications
4
67
0
Order By: Relevance
“…It can be expected that, at the atomic to meso scales, interaction of the different phases (B2 and B19) with the free surfaces causes significant variation in the phase fraction evolution process and transformation kinetics, as briefly addressed in recent computational studies by the authors [8,15]. However, in those previous studies by authors [8,15], as well as in some other relevant studies [11,13], the coupled effect of grain size and length scale, on the thermally induced martensitic phase transformation (MPT) was not addressed. Rather, all those previous studies [8,11,13,15] mainly explore the effects of the side length (thin samples of constant thickness i.e.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It can be expected that, at the atomic to meso scales, interaction of the different phases (B2 and B19) with the free surfaces causes significant variation in the phase fraction evolution process and transformation kinetics, as briefly addressed in recent computational studies by the authors [8,15]. However, in those previous studies by authors [8,15], as well as in some other relevant studies [11,13], the coupled effect of grain size and length scale, on the thermally induced martensitic phase transformation (MPT) was not addressed. Rather, all those previous studies [8,11,13,15] mainly explore the effects of the side length (thin samples of constant thickness i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Along the same lines, it has been observed that due to the evolution of different variants of B19 and B2 phases, the phase transformation process becomes inherently stochastic in nature [1,3,8] and occurs hierarchically over a very wide range of spatiotemporal scales [1,3,8,15]. However, the ins and outs of such aspects remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations